Hospital readmission after heart valve surgery in the United KingdomCentral MessagePerspective - Jeremy Chan, MD; Pradeep Narayan, MD; Tim Dong, BSc; Daniel P. Fudulu, MD, PhD; Gianni D. Angelini, MD (JTCVS Open)
Objective: To evaluate hospital readmission rates in the United Kingdom within the first 12 months following heart valve surgery. Methods: All patients who underwent heart valve surgery between January 2013 and April 2023 were included in the study. Readmission to any National Health Service hospital within 12 months after discharge was captured. Trends in readmission, primary and secondary diagnoses, and related procedures were evaluated. Results: A total of 44,467 patients (median age, 69.3 years; 61% male) were included, of whom 44.6%, 23.15%, and 11.95% experienced 1, 2, and 3 readmissions, respectively, within 12 months of discharge following the index procedure. The overall 30-day and 12-month readmission rates were 12.9% and 44.6%, respectively, with a total of 42,151 readmissions. The median time from discharge to readmission was 61 days (interquartile range, 14-168 days). The overall 12-month readmission rate remained consistently above 40% throughout the study period, with a slight drop in 2020 during the COVID-19 pandemic. Cardiovascular-related readmissions accounted for 10,318 (24.5%) of the total readmissions. Arrhythmia was the most common primary diagnosis (37.6%; atrial fibrillation/flutter in 82.4% of the cases), followed by heart failure (16.1%) and valve-related dysfunction (15.2%). Surgical valve procedure-related readmissions accounted for 24.9% of the total, with chest pain of noncardiac origin (41.0%), respiratory tract infections (16.0%), and pleural effusions (10.0%). Conclusions: Nearly one-half of the patients required at least 1 readmission within 12 months of heart valve surgery, placing significant strain on the healthcare system. Cardiovascular- and procedure-related causes accounted for one-half of all readmissions.